Recurrence of spondylarthropathy among first-degree relatives of patients: a systematic cross-sectional study. Issue 4 (15th April 2008) - Dernis, E; Said-Nahal, R; D'Agostino, M-A; Aegerter, P; Dougados, M; Breban, M
Abstract : Objective: To examine the recurrence of manifestations belonging to the spectrum of spondylarthropathy (SpA) in first-degree relatives of patients with SpA, and to estimate the recurrence risk ratio. Methods: Parents and siblings of consecutive SpA probands have been thoroughly investigated, including clinical data collection, pelvic x ray and human leukocyte antigen (HLA)-B27 status determination. The diagnosis of SpA was made according to European Spondylarthropathy Study Group and/or the Amor criteria. The recurrence risk ratio λ1, which gives an estimate of the weight of genetic factors, was calculated as the ratio of the recurrence risk of SpA in first-degree relatives compared with the population prevalence of SpA. The λnon-HLA was obtained by similar calculations restricted to HLA-B27+ individuals. Results: Most manifestations of SpA were more frequent among the 157 HLA-B27+ relatives of 83 probands than among their 111 HLA-B27- relatives. A diagnosis of SpA was made in 50 relatives of 31 (37%) probands. Recurrence was very similar between parents and siblings, without gender difference, resulting in overall recurrence risk of 12% in first-degree relatives and of 22.7% in HLA-B27+ relatives. The λ1 value was 40 and the λnon-HLA value was 6.5, very close to the λHLA value of 6.25 estimated from linkage study in SpA. Conclusions: A similar recurrence risk of SpA was observed between parents and siblings, consistent with a model of inheritance with no dominance variance and without sex influence. The weight of the non-HLA genetic component was equivalent to that estimated for the HLA locus, and fitted a model of multiplicative interaction between HLA and non-HLA genetic components.